PEMANFAATAN MEDIA LINGKUNGAN SEKITAR PADA PEMBELAJARAN SENI MUSIK MATERI MUSIK RITMIS SISWA KELAS IV SD NEGERI 2 ARGOTIRTO - Finka Fitriana Sari; Andika Gutama; Cicilia Ika Rahayu Nita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The use of environmental media is one way to present rhythmic music learning materials to students. The purpose of this study was to determine how environmental media is implemented and the obstacles faced by students in learning rhythmic music for fourth-grade students at SD Negeri 2 Argotirto. The method used was descriptive qualitative research. Respondents were teachers and fourth-grade students at SD Negeri 2 Argotirto. Data collection techniques included observation, interviews, and documentation. The data analysis technique used was Miles and Huberman's qualitative research analysis. Based on the research results, the use of environmental media in learning rhythmic music can increase student interest, creativity, collaboration, and understanding of the material, as evidenced by students' enthusiasm for the learning process. However, obstacles encountered in this study were the time-consuming process of creating environmental media. The researcher's recommendation to teachers is that the use of environmental media can be used as a learning medium to assist teachers in developing creativity in teaching rhythmic music, and the learning evaluation process can be conducted in a more enjoyable and engaging manner for students.